Pelatihan Tabuh Sekatian Di Desa Banjarangkan Kabupaten Klungkung | Tabuh Sekatian Training in Banjarangkan Village, Klungkung Regency - Agus, Komang Agus Arya Chandra (GHURNITA: Jurnal Seni Karawitan, 2024)
Tabuh Sekatian training is a program created by the author to provide character education by fostering interest and improving the skills of children and youth in Banjarangkan village. This program relates to assignments in the sixth semester, namely Thematic KKN activities. Through the Thematic KKN program, the author tries to strengthen the arts through percussion training activities and improve problems, especially musical art, in Banjarangkan Village. The methods used by the author in organizing this program are observation, practice, literature study, interviews, and discography to support this activity's plan. In holding this activity, several findings became problems, such as a lack of understanding of the basic techniques of playing gamelan and a decline in children's interest in playing gamelan. Therefore, the author plans to carry out KKNT activities to revive art and strengthen traditional traditions, which are still part of social life in Bali. By choosing percussion Sekatian as a learning reference, it is hoped that this training activity will not only add material but also introduce other regional arts to the people of Banjarangkan Village.